5PSQ-108 Reducing errors of oral medication administration in patients with dysphagia - Molina, M (Eur J Hosp Pharm, 2018)
BACKGROUND: Dysphagia is a prevalent difficulty among ageing adults predominately because of conditions such as stroke or dementia. In patients over 65-years-old, the prevalence of dysphagia ranges from 7% to 13%. To ensure safety during oral medication administration, patients require an appropriate oral dosage form. PURPOSE: The aim of this study was to avoid errors of oral medication manipulation and administration in dysphagic patients. MATERIAL AND METHODS: A prospective longitudinal study was performed for 2 months in the Internal Medicine Unit. Using a computerised physician order entry program, pharmacists detected inpatients with dysphagia, reviewed prescription to identify inadequate dosage forms and checked the manipulation of solid oral dosage forms. Data collected were: age, sex, number of medications prescribed by patient, liquid or dispersible oral formulations, solid oral formulations prescribed that required a previous manipulation, administration errors, pharmaceutical interventions during prescription or administration and percentage of acceptance. Data were analysed using Microsoft(®) Excel. RESULTS: Pharmacotherapy of 54 inpatients was analysed. Median age was 82 (55–99) years and 29 (54%) were females. Each patient received, on average, 12 different medications. Seventy-seven per cent of oral medications prescribed were not in an appropriate dosage form. Pharmacists made 64 interventions to ensure a safe administration and 52 (81%) were accepted by nurses. A total of 20 (12 during the first month) administration errors were detected. Pharmacists made 25 interventions to recommend alternative solid dose formulations, switch to liquid or dispersible oral formulations, alternative routes or change medication: 20 of these (80%) were accepted by physicians. During the first month the intervention’s acceptance rate was 67% by nurses and 50% by physicians, and during the second month it was 90% and 60% respectively. CONCLUSION: Most oral medications (77%) prescribed to dysphagic patients were manipulated. This fact can promote administration errors. We detected 20 errors because of manipulation of medicines that should never be crushed or opened. We have observed an improvement in the intervention’s acceptance, increasing from 67% to 90% in administration and 50% to 60% in prescription. Administration errors were reduced in 20%, therefore, pharmacists play an important role in medicines’ optimisation in patients with dysphagia. REFERENCES AND/OR ACKNOWLEDGEMENTS: Pharmacy, rehabilitation and internal medicine units staff. No conflict of interest